Zoonotic potential of currently circulating avian influenza viruses : Zoonotski potencijal trenutno cirkulirajućih virusa ptičje gripe - Savić, Vladimir, veterinar (Array, 2020)
Over the past and the current centuries, human influenza pandemics have been attributable to viruses with an avian ancestry. Birds are the main source of influenza A viruses and harbour a variety of antigenic subtypes. Certain avian influenza viruses are capable for cross-species transmission including human infections. Although sustained intrehuman transmission of such viruses has not been documented so far, each human infection with avian influenza viruses provides chances for the virus adaptation towards efficient transmission within human population. Here are reviewed currently circulating avian influenza viruses that are of major significance for public health.